The Paradigm of Islamic Legal Products in Indonesia: A Critical Review of the Polarization of the Characteristics and Authority of the Madhhab of Thought Products - Kurniati; Nur Khaera; Rahman, Abdul (Universitas Islam Negeri Alauddin Makassar, 2022)
Islamic law grows in Indonesia and is formulated in four legal thought products, namely fiqh, jurisprudence, law, and fatwa. The problematic Application of Legal Products is more related to the internal aspects of Muslims, who are less dynamic and pay less attention to the developing problem. Therefore, a huge difference occurs between static Islamic and dynamic western legal products using a normative approach. The results showed that Islamic legal products resulted from the work of ijtihad, fiqh, and Islamic law experts. Each Islamic legal product has characteristics and particularities, and the application implicitly raises problems. However, Islamic legal products have been applied explicitly as the law regulates. The products have reliable binding power through a fatwa, judges’ decisions, and critical reviews have increased diversity awareness. The results of the fatwa provided many legal answers to the problems, and the establishment of Religious Courts facilitates justice seekers in solving legal issues. The position of legalized Islamic law is strengthened, and a more profound elaboration is needed to analyze the polarization of product authority.